Self-managed physical activity in breast cancer survivors: A scoping review. - Maria Chiara Bò; Andrea Merlo; Maria Bernadette Ligabue; Maria Chiara Bassi; Mirco Lusuardi; Isabella Campanini (PLoS ONE)
Objective Breast cancer survivors (BCS) experience many issues of rehabilitative concern due to the treatments they have undergone. Given the chronicity of these outcomes, the increasing number of survivors, and the positive results obtained by supervised exercise, professionals should consider offering self-managed physical activity (PA) programs to this population. Our aim was to map the currently available evidence about self-care rehabilitation for BCS. Methods Medline, CINAHL, and Cochrane databases were searched for primary literature. Scoping review methodological frameworks were used to tackle the heterogeneity of the topic. Studies investigating self-managed PA interventions prescribed to adult BCS were included. Results One hundred-eight studies were included, with sample sizes ranging from 6 to 692 patients. Information was systematically collected in tables displaying study design, type of PA, duration and recommended frequency, professional leading the study, type of supervision, initial training, strategies used to help patients integrate self-care into their daily lives, and self-managed PA efficacy. Tables were produced for every oncological side effect that BCS might experience: lymphedema, arthralgia, cancer-related fatigue, a decline in physical parameters, treatment-related cardiotoxicity, peripheral neurotoxicity, and a possible decline in the quality of life. Conclusions Self-managed PA has the potential to improve BCS oncological issues. Professionals can adopt many strategies to support patients and empower them with long-lasting self-care competencies. This scoping review provided a comprehensive and easy-to-consult overview of self-managed PA interventions for BCS. We also provided recommendations for future primary studies and secondary synthesis.